Odpowiedź :
x - waga borsuka
y - waga lisa
x = 2y - 5
2x = 3y
x = 2y - 5
2(2y - 5) = 3y
x = 2y - 5
4y - 10 = 3y
x = 2y - 5
4y - 3y = 10
x = 2 * 10 - 5
y = 10
x = 20 - 5
y = 10
x = 15
y = 10
Borsuk waży 15 kg, a lis 10.
y - waga lisa
x = 2y - 5
2x = 3y
x = 2y - 5
2(2y - 5) = 3y
x = 2y - 5
4y - 10 = 3y
x = 2y - 5
4y - 3y = 10
x = 2 * 10 - 5
y = 10
x = 20 - 5
y = 10
x = 15
y = 10
Borsuk waży 15 kg, a lis 10.
x - waga borsuka,
y - waga lisa'
2x = 3y
2y = x + 5
2x = 3y
-2x = 10 - 4y
-10 = -y
10 = y
y = 10
x = 15
Odp: Borsuk waży 15 kg :)
y - waga lisa'
2x = 3y
2y = x + 5
2x = 3y
-2x = 10 - 4y
-10 = -y
10 = y
y = 10
x = 15
Odp: Borsuk waży 15 kg :)
x - borsuk
y- lis
2x=3y / :2
2y=x+5
x=1,5y
2y=x+5
x=1,5y
2y=1,5y+5
x=1,5y
2y-1,5y=5
x=1,5y
0,5y=5 /:0,5
x=1,5y
y=10
x=1,5*10
y=10
x=15
y=10
Borsuk waży 15kg
y- lis
2x=3y / :2
2y=x+5
x=1,5y
2y=x+5
x=1,5y
2y=1,5y+5
x=1,5y
2y-1,5y=5
x=1,5y
0,5y=5 /:0,5
x=1,5y
y=10
x=1,5*10
y=10
x=15
y=10
Borsuk waży 15kg